2008
DOI: 10.1183/09031936.00092507
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of community-acquired pneumonia: influence of age, residence status and antimicrobial treatment

Abstract: Community-acquired pneumonia remains a major cause of mortality in developed countries. There is much discrepancy in the literature regarding factors influencing the outcome in the elderly population.Data were derived from a multicentre prospective study initiated by the German Competence Network for Community-Acquired Pneumonia. Patients with community-acquired pneumonia (n52,647; 1,298 aged ,65 yrs and 1,349 aged o65 yrs) were evaluated, of whom 72.3% were hospitalised and 27.7% treated in the community. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
103
2
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 41 publications
12
103
2
14
Order By: Relevance
“…13,14 Pneumonia is also the most common cause of death in patients with acute stroke, 15 and it occurs more frequently than expected in dementia patients, 7,16 and in patients with solid cancers. 11,17,18 Given the uncertainty regarding the effectiveness of pneumococcal vaccination, 19 and in the presence of increasing morbidity due to pneumonia, GPs need to be able to identify and closely monitor those patients at highest risk of pneumonia. For example, such patients might benefit from earlier intervention with antibiotics when they present to their GP with a chest infection.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Pneumonia is also the most common cause of death in patients with acute stroke, 15 and it occurs more frequently than expected in dementia patients, 7,16 and in patients with solid cancers. 11,17,18 Given the uncertainty regarding the effectiveness of pneumococcal vaccination, 19 and in the presence of increasing morbidity due to pneumonia, GPs need to be able to identify and closely monitor those patients at highest risk of pneumonia. For example, such patients might benefit from earlier intervention with antibiotics when they present to their GP with a chest infection.…”
Section: Introductionmentioning
confidence: 99%
“…Kothe ve arkadaşlarının çalışmasında, ampirik olarak beta-laktam ± makrolid veya solunum florokinolonları başlanan hastalarda 65 yaş altı 1.298 hastanın %25.4'ünde ve 65 yaş üstü 1.349 hastanın %32.6'sında tedavi başarısızlığına bağlı başlangıç antibiyotik tedavisinde değişiklik yapılmıştır (24).…”
Section: Discussionunclassified
“…Other authors have reported the association of comorbidities and guideline-discordant antibiotic therapy with mortality. (7,28) The present study has limitations, which should be pointed out. It is possible that the retrospective design contributed to the significant loss of information that might have changed the results obtained.…”
Section: Discussionmentioning
confidence: 99%